ANALYZING THE IMPACT OF STOCK TURNOVER AND CASH FLOW ON THE NET PROFIT MARGIN OF PT INFINEON TECHNOLOGIES BATAM - Baru Harahap; Syahril Effendi; Ronald Wangdra (Universitas Putera Batam, 2023)
The objective of this study is to investigate how the earnings of PT Infineon Technologies Batam were impacted by stock turnover and cash flow between 2018 and 2022. The R Square test findings indicate that 20.8% of the net profit margin can be attributed to the stock turnover and cash flow variables, while the remaining 29.2% is explained by other unexamined factors. The t-test results reveal that the number of inventories has a significant negative effect on the net profit margin, as evidenced by a value of less than -2.299 and a significant level of 0.002 < 0.05. Similarly, the cash flow variable had a significant negative effect on the net profit margin, as evidenced by a t-test value of 3.159 and a significant level of 0.001 < 0.05.